Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia - Bayarsaikhan, Ulziijargal; Lee, Dong˗june; Bae, Yang˗seop (Zootaxa, 2018)
Three new species of the genus Diduga, D. dubatolovi n. sp., D. kohkongensis n. sp., and D. bispinosa n. sp. are described from Cambodia along with other five recorded species, D. albicosta Hampson, 1891, D. barlowi Holloway, 2001, D. amoenusa Bucsek, 2012, D. annulata Hampson, 1900, and D. alternota Bucsek, 2014. A key to the Cambodian species of the genus Diduga with illustrations of adults and genitalia are presented.